Interação entre as políticas fiscal e monetária brasileiras no período pós-Plano Real: uma análise de causalidade com aplicação do modelo VAR - Machado, Joanito Teixeira (2010)
This study consists in the analyses of the relations of causality among some of the main variables of Brazilian fiscal and monetary policies in the period post-Plano Real (1995-2008). The study was concentrated in the identification of the impacts of each one of the variables over the determination of the temporal path of each another. Initially, the work systematizes the theorist debate about the subject in two divergent axes: i) The hypothesis of fiscal dominance, that identificates the main determinants of the persistent contracionist monetary policy in the expansionist fiscal policy. ii) An alternative hypothesis that identificates the main determinants of the fiscal disequilibrium of the public sector in Brazil in the contracionist monetary policy, in the persistent overvaluation of the Real and in the strategy of international insertion of the country in the last two decades. Even, the study presents an econometric analyses of temporal series about fiscal policy, monetary policy and exchange rate policy in Brazil in the period of January/1995- December/2008. The econometric analyses consists in the application of the Vector Autorregressive Model (VAR) and of the Granger Causality Test